ANALISIS PEMASARAN CABAI RAWIT DI DESA SIWALEMPU KECAMATAN SOJOL KABUPATEN DONGGALA - Riadi, Agus; Kassa, Saharia; Effendy, Effendy (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2023)
The main objectives of this research were to examine the various marketing channel of cayenne pepper, to assess the percentage of the price received by farmers (producers) in every channel, and to evaluate the marketing efficiency of cayenne pepper in Siwalempu village, Sojol sub district, Donggala district. A total of 40 respondents participated in the study, selected using a simple random sampling method. The chili commodity in Siwalempu Village was found to be marketed through two different channels. The first channel involves the sequence: Producers → Collectors → Retailers → Consumers, and in this channel whereas the second channel operates as follows: Producers → Retailers → Consumers. The farmers in the channel 2 received 91% of the final price paid by consumers greater than the farmers received in the channel 1 (87%). Additionally, it was observed that the channel 2 has a shorter marketing process compared to channel 1. The research revealed that the channel 2 exhibits higher marketing efficiency, with a value of 3.08%, while channel 1 marketing efficiency calculated was 2.24%. Therefore, channel 2 is considered to be more efficient in the marketing of cayenne pepper compared to the channel 1.